Rancang Bangun Sistem Informasi Pelelangan Ikan (Studi Kasus TPI Majakerta Indramayu) - Riyan Farismana; Alien Agnestia; Moh. Ali Fikri; Dian Pramadhana; Darsih (UM Purwokerto Press, 2026)
Indramayu's position as the number one fish producer in West Java, in addition to the presence of 14 fish auction places (TPI) in Indramayu should make the price of fish better and provide additional economic benefits for fishermen. The problem that has arisen so far is that the facilities are said to be inefficient so that fishermen are forced to sell outside the TPI to maintain the freshness of the fish at uncompetitive prices. TPI Majakerta is one of the TPI that has similar problems plus the administrative process at TPI Majakerta, starting from recording the catch, announcing the bid price, to compiling the auction report, is still done manually using paper and direct recording by officers which is prone to errors. This research is intended to create a website-based fish auction system in Indramayu where the case study was conducted at TPI Majakerta. The research began with requirements, analysis, design, to implementation by creating a system prototype. The result is there are three main users: admin, auctioneer, and service. With an auction system similar to an auction at TPI, where buyers submit bids through the system, where there is a time running during the auction process and the highest bid becomes the auction winner.